2004
DOI: 10.1002/ijc.20263
|View full text |Cite
|
Sign up to set email alerts
|

Risk of esophageal, ovarian, testicular, kidney and bladder cancers and leukemia among finnish workers exposed to diesel or gasoline engine exhaust

Abstract: Occupational exposure to diesel exhaust has been classified as probably carcinogenic and that to gasoline engine exhaust as possibly carcinogenic to humans. Earlier results concerning cancers other than lung cancer are scarce and inconsistent, and exposure-response relations have seldom been reported. We followed up a cohort of all economically active Finns born between 1906 and 1945 for 30 million person-years during 1971-1995. Incident cases of esophageal cancer (n ‫؍‬ 2,198), ovarian cancer (5,082), testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 29 publications
2
52
1
2
Order By: Relevance
“…also been associated with AML in earlier studies [144], but it is hard to observe any effects of these factors from the present results. Drivers and sales agents, who had significantly elevated SIRs for AML in the present study have also been previously reported to have a somewhat elevated risk of AML [143,145].…”
Section: Leukaemiasupporting
confidence: 69%
“…also been associated with AML in earlier studies [144], but it is hard to observe any effects of these factors from the present results. Drivers and sales agents, who had significantly elevated SIRs for AML in the present study have also been previously reported to have a somewhat elevated risk of AML [143,145].…”
Section: Leukaemiasupporting
confidence: 69%
“…The original studies established a positive dose-response relationship between exposure to diesel engine exhaust and ovarian cancer. A Finnish study (Guo J, et al, 2004) has reported that the increased relative risk was driven by a cohort of workers exposed to grease on car components. These studies may need careful consideration about the use of gender specific risk estimates.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Most of the study areas were large cities and the surrounding suburban or rural communities, as specified in the online appendix (pp. [4][5][6][7][8][9][10][11][12][13]. A pooled analysis of all cohort data was not possible due to data-transfer and privacy issues but data from the four Stockholm cohorts (SNAC-K, SALT, 60-y/IMPROVE and SDPP) were pooled, and analysed and denoted as one Similarly, data from the two cohorts from the Netherlands (EPIC-MORGEN and EPIC-PROSPECT) were pooled, analysed and denoted as one [EPIC-NL].…”
Section: Design and Participantsmentioning
confidence: 99%